Integrasi Ajaran Tasawuf dan Psikologi Kepribadian dalam Naskah Serat Tasawuf: Telaah Interdisipliner terhadap Pembentukan Insan Kamil - Kosasih, Ade (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to explore the moral and spiritual teachings embedded in Serat Tasawuf, a classical Sundanese manuscript written in Pegon script, which represents an important part of the Islamic manuscript heritage in the Indonesian archipelago. The text presents a systematic exposition of Sufi teachings, including the ethical obligation to guard bodily faculties, avoid blameworthy inner traits, and cultivate virtuous character. Employing a descriptive qualitative approach with a comparative analytical method, the study integrates philological analysis with perspectives from personality psychology. The findings reveal that the structure and substance of Serat Tasawuf align with Erich Fromm’s theory of productive character and Gordon Allport’s concepts of trait and psychological maturity. The manuscript not only offers individual spiritual guidance but also emphasizes social values such as empathy, simplicity, and resilience in the face of life’s trials. Thus, Serat Tasawuf can be positioned as a relevant Sufi text for the development of an ideal personality (insan kamil) in contemporary society. This interdisciplinary study makes a significant contribution to the development of character education models grounded in local Islamic manuscripts and humanistic psychology.